Re-evaluating sharpe ratio in hedge fund performance in light of liquidity risk - Richard van Horne; Katarzyna Perez (Journal of Banking and Financial Economics (JBFE), 2021)
This paper demonstrates how the Sharpe Ratio can be modified by altering the measure of "total risk" in the denominator of the Sharpe Ratio (i.e., the standard deviation) to include liquidity risk, a major risk for investors in hedge funds that is missing from the standard Sharpe Ratio formulation. We refer to our liquidity-risk-adjusted performance ratio as the LRAPR. The results of our analysis of 1186 hedge funds alive in 2012-2020 show that funds with higher liquidity risk exhibit higher Sharpe Ratios and higher Alphas (as estimated in a 7-factor model that does not incorporate liquidity risk). We posit that analysts and investors should not necessarily take these higher Sharpe Ratios and higher Alphas as indications of fund superiority; what appears to be superior manager skill may rather be a compensation for bearing liquidity risk. Our LRAPR is a tool that analysts or investors could use to compare funds on a more equal footing, adjusting for differential liquidity risk across funds.
Keywords: G12; G23; C18; 330; liquidity risk; liquidity rist factor; serial correlation; Sharpe ratio; hedge fund performance